2000
DOI: 10.1007/s11906-000-0053-8
|View full text |Cite
|
Sign up to set email alerts
|

Heredity and the autonomic nervous system in human hypertension

Abstract: Because the complex phenotype of human hypertension is at least in part genetically determined, how individual genes ultimately contribute to the disease is not well understood. By contrast, intermediate phenotypes are traits associated with complex disease, but which may display simpler genetic properties such as greater heritability, more consistent and earlier penetrance and bimodality, and may suggest particular candidate susceptibility genes. Because autonomic nervous system activity is altered in hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 62 publications
0
69
0
Order By: Relevance
“…[2][3][4][5] The autonomic nervous system plays a central role in minute-to-minute control of blood pressure, and heritable alterations in autonomic function are associated with hypertension. 6 Therefore, we sought to assign chromosomal positions for loci encoding crucial components of the sympathetic neuroeffector junction (Figure 1), in order to facilitate studies of the genetic underpinnings of autonomic alterations in hypertension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] The autonomic nervous system plays a central role in minute-to-minute control of blood pressure, and heritable alterations in autonomic function are associated with hypertension. 6 Therefore, we sought to assign chromosomal positions for loci encoding crucial components of the sympathetic neuroeffector junction (Figure 1), in order to facilitate studies of the genetic underpinnings of autonomic alterations in hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] The autonomic nervous system is a key regulator of minute-to-minute changes in blood pressure. 6 Autonomic dysfunction in hypertension seems to be heritable [6][7][8][9][10][11][12][13] and alterations in autonomic activity may precede overt hypertension in subjects at genetic risk of the syndrome. [6][7][8][9][10][11][12][13] Previous allelic association (ie, case/control) studies in hypertension have documented the role of allelic variation (or allele frequency differences) at adrenergic receptor loci (ADRB2, 14,15 ), postreceptor signal transduction component loci (GNAS1 16 , and GNB3 17 ), and catecholamine biosynthetic enzyme loci (TH 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The catecholamines norepinephrine (NE) and epinephrine (E) mediate the early stress response via the sympathetic nervous system, 1,2 but they also have a key role in homeostatic blood pressure (BP) control 3,4 through the activation of adrenergic receptors located on the heart and the blood vessels. It has been suggested that abnormally increased sympathetic function may lead to the development and progression of a hypertensive state 3,5 perhaps initially by influencing transient BP increases to environmental stress.…”
Section: Introductionmentioning
confidence: 99%
“…15 In this association analysis, we evaluated allele and genotype frequencies of single nucleotide polymorphisms (SNPs) individually and in combination, in the form of haplotypes at CHGA; we compared such gene and haplotype frequencies in normotensive and hypertensive black controls (with normal renal function) to those in black patients with ESRD as a result of hypertension (HT-ESRD). In addition, we evaluated the impact of CHGA SNPs on a more proximate or "intermediate" biologic phenotype, 16 expression of the catestatin gene product in plasma.…”
mentioning
confidence: 99%